2022
DOI: 10.1038/s41531-022-00408-6
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of genetic testing for Parkinson’s disease in the clinical setting

Abstract: Parkinson’s disease (PD) guidelines lack clear criteria for genetic evaluation. We assessed the yield and rationale of genetic testing for PD in a routine clinical setting on a multicenter cohort of 149 early-onset and familial patients by exome sequencing and semi-quantitative multiplex ligation-dependent probe amplification of evidence-based PD-associated gene panel. We show that genetic testing for PD should be considered for both early-onset and familial patients alike, and a clinical yield of about 10% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In most populations, there is still a lack of genetic studies that include patients in all possible onset types of PD and often focus on patients with a positive family history of PD or an early onset of the disease. A study has been published involving several patients from this cohort as part of a larger group of patients with early and familial onset from Croatia, Slovenia, and Serbia, where GBA was the most common causative genetic factor for the development of Parkinson's disease, with a higher percentage of patients with causative variants, possibly because sporadic patients were not included [17]. Similar results are observed in neighboring Italy, in an isolated population in Sardinia, where GBA and PRKN variants were the most common but in a smaller percentage than in our study (4.4%) [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most populations, there is still a lack of genetic studies that include patients in all possible onset types of PD and often focus on patients with a positive family history of PD or an early onset of the disease. A study has been published involving several patients from this cohort as part of a larger group of patients with early and familial onset from Croatia, Slovenia, and Serbia, where GBA was the most common causative genetic factor for the development of Parkinson's disease, with a higher percentage of patients with causative variants, possibly because sporadic patients were not included [17]. Similar results are observed in neighboring Italy, in an isolated population in Sardinia, where GBA and PRKN variants were the most common but in a smaller percentage than in our study (4.4%) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, information on the expected diagnostic yield of genetic testing is important for informing clinical decisions. To address this issue, we recently published a collaborative next-generation sequencing (NGS) genetic study in EO and FO PD patients from the Serbian, Slovenian, and Croatian populations, the first South Slavic population study [17].…”
Section: Introductionmentioning
confidence: 99%
“…NGS requires significant investment (sequencers and computer servers), needs bioinformaticians and its analysis time is much longer. Other studies used different NGS methods in PD [21, 26] or early‐onset PD [22, 27]. All pathogenic variants (excluding GBA variants that are risk factors for PD) described in Illés et al [21] and Kovanda et al [26] could be observed using MLPA ± Sanger sequencing to look for a second mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Between January 2014 and July 2019, 27 individuals underwent clinical exome sequencing and between July 2019 and December 2022, 93 individuals underwent exome sequencing. Sequencing and data analysis were performed at our institute as previously described [35][36][37]. For clinical and exome sequencing, the median minimum exome coverage was 60x, with more than 95% of the targets covered with at least 10x sequencing depth.…”
Section: Sequencing and Bioinformatics Analysismentioning
confidence: 99%